2016
DOI: 10.1007/s13105-016-0524-2
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocotrienol prevents cell cycle arrest in aged human fibroblast cells through p16INK4a pathway

Abstract: Human diploid fibroblasts (HDFs) proliferation in culture has been used as a model of aging at the cellular level. Growth arrest is one of the most important mechanisms responsible for replicative senescence. Recent researches have been focusing on the function of vitamin E in modulating cellular signaling and gene expression. Therefore, the aim of this study was to elucidate the effect of palm γ-tocotrienol (vitamin E) in modulating cellular aging through p16 pathway in HDF cells. Primary culture of senescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…In this study, Hsp70 was upregulated in γT3-treated senescent cells compared with vehicle-treated senescent cells. Our results suggest that γT3 may increase the stress response of senescent cells which accounts for its pro-survival effect on senescent cells as observed in previous study [ 15 ]. Cells isolated from aged organisms or undergoing replicative senescence have reduced heat shock response.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In this study, Hsp70 was upregulated in γT3-treated senescent cells compared with vehicle-treated senescent cells. Our results suggest that γT3 may increase the stress response of senescent cells which accounts for its pro-survival effect on senescent cells as observed in previous study [ 15 ]. Cells isolated from aged organisms or undergoing replicative senescence have reduced heat shock response.…”
Section: Resultssupporting
confidence: 85%
“…Written consents were obtained from their parents with Ethical approval code: FF-249-2012. The isolation, culture and passaging of HDFs were performed as described previously [ 15 ]. Briefly, epidermis of the skin was removed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that TRF treatment of senescent fibroblast cells increased the expression of telomerase and enhanced the elongation of telomere [ 26 ]. Furthermore, γ-tocotrienol treatment of senescent cells downregulates p16, cyclin D1 and hypophosphorylated-Rb, all of which are involved in cell cycle arrest [ 32 ]. Thus, TRF is postulated to modulate telomerase expression, increase the expression of proteins involved in cell cycle to prevent cell cycle arrest and promote proliferation of myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, Zainuddin et al found overexpression of P16 (INK4a) mRNA in human diploid broblasts [18]. Hypertrophic LF hyperplasia is caused by excessive proliferation of broblasts and imbalance of elastic/collagen ber ratio [19].…”
Section: Discussionmentioning
confidence: 97%